(untitled) (Research, Society and Development, 2021)
Considering the current global situation, marked by major crises in public health and, more recently, the pandemic caused by COVID-19, the present study aimed to analyze the biopsychosocial changes resulting from the social isolation caused by the Pandemic in dentistry students from University of Pernambuco. Regarding the methodology, it was a field survey of quantitative analysis, cross-sectional and descriptive. The sample consisted of a universe of 379 students, 106 of whom participated in the study. The collection was carried out over a period of 72 hours, in June 2021, where students answered an online questionnaire developed through the Google Forms platform containing closed and open questions about sociodemographic data, as well as aspects related to physical and psychosocial changes . The results suggest that in the sample studied, social isolation had repercussions on the daily routine, many reported problems with concentration, sleep disorders, feelings of fear, worry and sadness. It was concluded that the majority of respondents were female, the prevalent age group was 18 to 24 years old, they live with 2 or 4 more people in their homes, are single and reported having had financial losses with the pandemic. Among the main psychosocial issues, the following stood out: low performance in daily activities; routine modifications; lack of concentration; sleep disorders, psychological disorders and fear.